The fishing moratorium regime under the framework of global marine governance: insights from China - Yuan, Wei; Pan, Xuejiao (Frontiers in Marine Science, 2025)
More than four decades after the adoption of the United Nations Convention on the Law of the Sea (UNCLOS), global marine living resources have seen enhanced protection, yet a significant proportion remain under severe strain. Fisheries resources, inherently renewable, now face compromised sustainability due to expanding economic activities and ever-increasing human demands. Current solutions—such as establishing marine protected areas, combating Illegal, Unreported, and Unregulated (IUU) fishing, and forming fisheries management organizations—address certain aspects of resource conservation but lack precision. This study is based on a systematic review of Chinese legal instruments, ministry notices and national fishery statistics (CMARA, China Fishery Statistical Yearbook) and relevant international instruments. From the perspective of global ocean governance, this study analyzes the origins, implementation, and innovations of China’s fishing moratorium system, proposing actionable and globally scalable recommendations. The aim is to advance targeted and efficient strategies for sustaining fishery resources and strengthening global ocean governance.